2008
DOI: 10.2174/1874456700802010022
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Isotopic Variations in the Clinopyroxene from the Filicudi Volcanic Rocks (Aeolian Islands, Italy): Implications for Open-System Magma Evolution

Abstract: Oxygen isotope data are reported for clinopyroxene phenocrysts from volcanic rock samples from Filicudi island, Italy, with the aim of investigating mechanisms of magma evolution and mantle source characteristics in a continental arc volcano. Filicudi rocks range from calc-alkaline basalt to high-K andesite and dacite. Mafic rocks have MgO 6-7 wt%, Mg# 60, Ni < 50 ppm and Cr < 200 ppm, suggesting they represent evolved melts from more primitive mantle-derived parents. Variations of Sr-Nd isotope ratios against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…lower Sr-and O-and higher Nd -Pb isotope ratios) than associated basalts (Peccerillo & Wu 1992;Peccerillo et al 1993;Lucchi et al 2013a). The same process has been recognized, although less clearly, at Filicudi (Santo & Peccerillo 2008;Lucchi et al 2013b).…”
Section: Magma Contaminationmentioning
confidence: 63%
See 3 more Smart Citations
“…lower Sr-and O-and higher Nd -Pb isotope ratios) than associated basalts (Peccerillo & Wu 1992;Peccerillo et al 1993;Lucchi et al 2013a). The same process has been recognized, although less clearly, at Filicudi (Santo & Peccerillo 2008;Lucchi et al 2013b).…”
Section: Magma Contaminationmentioning
confidence: 63%
“…Several studies on Aeolian volcanoes demonstrated that magma -wall-rock interaction produced an increase in both 87 Sr/ 86 Sr and d 18 O‰ (Ellam & Harmon 1990;Peccerillo et al 2004;Santo & Peccerillo 2008). However, whereas O-isotope ratios were increased from typical mantle values of d 18 O‰ c. þ5.5 to values as high as d 18 O‰ c. þ8.5, Sr isotope ratios were less strongly modified.…”
Section: Magma Contaminationmentioning
confidence: 99%
See 2 more Smart Citations